2017
DOI: 10.21475/ajcs.17.11.10.pne473
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and path analysis for grain yield and chocolate spot disease resistance in faba bean (Vicia faba L.)

Abstract: This study was conducted to estimate better-parent and mid-parent heterosis for grain yield and chocolate spot resistance and to determine the direct and indirect effects of yield components on yield of faba bean (Vicia faba L.) in Ethiopia. Ten genetically diverse inbred lines were crossed in a full diallel to produce 90 F 1 progenies. The parents and their 90 F 1 progenies were evaluated in a 10 x 10 alpha lattice design with two replications at three locations. Data were analyzed using the Gardner and Eberh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As given in Table 4, seed yield/plant was positively and significantly correlated with each of pod length, number of pods/plant, number of seeds/pod, number of seeds/plant as well as 100-seed weight during the two seasons. In this respect, positive and significant association was recorded between seed yield with each of number of pods/plant, number of seeds/pod and 100-seed weight by many others (Ulukran et al, 2003;Ahmed et al, 2013;Sharifi, 2014;Verma et al, 2015;Jalal et al, 2016;Hamza, 2017;Hamza and Khalifa, 2017;Kumar et al, 2017;Tekalign et al, 2017). Also, Mitiku and Wolde (2015) showed that, number of seeds/pod with seed yield/plant was positively and significantly correlated.…”
Section: Correlation Coefficient Analysismentioning
confidence: 91%
“…As given in Table 4, seed yield/plant was positively and significantly correlated with each of pod length, number of pods/plant, number of seeds/pod, number of seeds/plant as well as 100-seed weight during the two seasons. In this respect, positive and significant association was recorded between seed yield with each of number of pods/plant, number of seeds/pod and 100-seed weight by many others (Ulukran et al, 2003;Ahmed et al, 2013;Sharifi, 2014;Verma et al, 2015;Jalal et al, 2016;Hamza, 2017;Hamza and Khalifa, 2017;Kumar et al, 2017;Tekalign et al, 2017). Also, Mitiku and Wolde (2015) showed that, number of seeds/pod with seed yield/plant was positively and significantly correlated.…”
Section: Correlation Coefficient Analysismentioning
confidence: 91%
“…Previous studies have reported the economic effects of heterosis on yield components, with hybrids having higher heterosis values than the parent for yield components and maturity stage in faba beans [25]. Additionally, Tekalign et al and Waly et al [38,39] reported significant heterosis in F1, which increased by 40% compared to the parents. Furthermore, the yield quantity and quality of F1 were higher than the mean values of better and mid parents [40].…”
Section: Heterosis Potency Ratio and Inbreeding Depressionmentioning
confidence: 92%